Electrochemical mechanisms of an advanced low-temperature fuel cell with a SrTiO3 electrolyte. Issue 16 (3rd April 2019) - Chen, Gang; Liu, Hailiang; He, Yang; Zhang, Linlin; Asghar, Muhammad Imran; Geng, Shujiang; Lund, Peter D.
Abstract : The electrochemical mechanisms and performance of a symmetrical low-temperature SOFC with a single oxide as the electrolyte are investigated here. Abstract : The electrochemical mechanisms and performance of a symmetrical low-temperature SOFC with a single oxide as the electrolyte are investigated here. The fuel cell has a layered Ni foam–Ni0.8 Co0.15 Al0.05 LiO2 (NCAL)/SrTiO3 (STO)/NCAL–Ni foam structure. A 0.8 mm thick layer of STO is used as the electrolyte and NCAL-coated nickel foam is used as the electrode on both sides of the cell. The maximum power densities of the cell were 0.31, 0.44, and 0.62 W cm −2 in a H2 /air atmosphere at 450, 500, and 550 °C, respectively. The corresponding ionic conductivities of the STO electrolyte were 0.16, 0.21, and 0.24 S cm −1 . Ion filtration experiments with densified Gd-doped CeO2 /STO and SrCe0.95 Y0.05 O3− δ /STO double layer electrolytes indicated that both oxygen ions and protons act as charge carriers in the STO electrolyte. XPS, TGA, and HRTEM analyses indicate that lithium carbonate, which originates from the NCAL, coats the STO electrolyte and forms a core–shell structure in the fuel cell test atmosphere. Lithium carbonate between the surface and interface of the STO particles may provide a pathway for oxygen ion and proton conduction.